The Need for Public Deliberation: Giving the Public a Voice on Affordable Health Insurance - Cook, Fay Lomax (Journal of health politics, policy and law, 2011)
Affordability is a key consideration in debates about the mandate for Americans to buy health insurance as required by the 2010 Patient Protection and Affordable Care Act. Yet no universally agreed-upon standard exists for determining what constitutes affordable health insurance. The question, then, is how best to make decisions about what is affordable. Adapted from the source document.